Biomaterials used in regeneration of salivary gland in three-dimensional culture system -a systematic review - M. Harinisubasri; Divya Bose; Dineshkumar Thayalan; Rajkumar Krishnan; Rameshkumar Annasamy (Oral Oncology Reports)
Background: Salivary gland dysfunction is caused by various pathological conditions including radiation therapy. Regeneration of the salivary gland components will pave a new path in restoring its function. Aim: This systematic review aims to illustrate the various bio-materials used as a scaffold in the 3-dimensional regeneration of the salivary gland. Materials and methods: Electronic databases like PubMed, Scopus, and Web of Science were used as search engines to search for articles related to various biomaterials used in the three-dimensional regeneration of salivary glands. Only original, full-length articles published in the English language were included for the review. Results: Totally 17 articles were chosen among which 15 articles were based on in vitro studies and the remaining 2 were based on in vivo studies. Biomaterials like hyaluronic acid-based, fibrin, Polyethylene glycol, Decellularized extracellular matrix hydro-gels, egg white-based scaffolds, and silk fibroin scaffolds have been tried. In 52.9% of the studies, Acinar components were formed along with the duct formation in 52.9% of the studies followed by the formation of the myoepithelial component in 29.4% of the studies with neuronal innervation only in 5.88% of the studies. Conclusion: Hyaluronic acid-based hydrogel scaffold proved to be a promising biomaterial that produced functional salivary glands in in-vitro conditions. However, more detailed studies under in-vivo conditions in the animal model could pave a new path for regularly using these bio-materials for regeneration methods.